PENGARUH BORAKS TERHADAP MOTILITAS DAN INTEGRITAS MEMBRAN SPERMA MENCIT (MUS MUSCULUS) - Yunilda Rosa; KHM Arsyad; Joko Marwoto (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2016)
Abstract: The use of food additive such as borax to preservative in food production process could be have a negative effects on health. The abuse of borax as food additive in the pempek and bakso can be dangerous for human health at Palembang city. The borax or boric acid have toxic effect on all body cells. The purpose of the research is to assess the effect of borax on the sperm motility and integrity of sperm membrane. Including to assess, how many are the borax doses can cause decrease the sperm motility and integrity of sperm membrane of mice. The research was carried out at laboratory Department of Medical biology, Faculty of Medicine Sriwijaya University Palembang using a Completely Randomized Design with six replications. Three treatment doses of the borax were prepared, i.e. 2 mg/10 gr bw, 4 mg/10 gr bw and 6 mg/10 gr bw for P2, P3 and P4 treatment groups of mice, respectively. Each group was consisted of six reproductive male mice and controlwith aquabidest were given each day, for 35 days. The control (P1) group was administrated by similar volume of aquabidest only. The result showed that borax could decreased very significantly (P<0,01) quality of mice sperm, especially sperm motility and integrity of sperm membran compared to control (P1) group. As a conclusion, the administration of borax at doses 2 mg/10 gr bw, 4 mg/10 gr bw and 6 mg/10 gr bw on male mice by gavage in 35 days can very significantly decrease the quality of mice sperm especialy decrease of the sperm motility and increase integrity of the sperm membrane (P<0.01) compared to the control group. It is suggested to conduct further studies such as the borax can used as one choice for the man contraception. Key words: Borax, Sperm Motility, Integrity of Sperm Membran and Mus musculus.